Analisis Putusan Pengadilan Federal Australia atas Kasus Montara dan Implikasinya terhadap Sengketa Pencemaran Laut Lintas Batas di Masa Depan - Rini Siti Juariah (Jurnal Hukum Lex Generalis, 2022)
The 2009 Montara case has caused losses to around 15,000 seaweed farmers in NTT. In 2021, the Australian Federal Court found PTTEP Australasia guilty and obliged to pay compensation. The judge's consideration is that he believes that the Montara oil spill did indeed reach Rote/Kupang and materially contributed to the damage to the seaweed. The judge found that PTTEP Australasia had a duty of care for the victims who were actually violated. This decision has the potential to set a precedent for transboundary marine pollution cases, trigger more environmental class action lawsuits, and demonstrate the need to establish an international convention regarding compensation for losses due to pollution caused by offshore oil businesses.